1999
DOI: 10.1121/1.427069
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic evidence for dynamic formant trajectories in Australian English vowels

Abstract: The extent to which it is necessary to model the dynamic behavior of vowel formants to enable vowel separation has been the subject of debate in recent years. To investigate this issue, a study has been made on the vowels of 132 Australian English speakers (male and female). The degree of vowel separation from the formant values at the target was contrasted to that from modeling the formant contour with discrete cosine transform coefficients. The findings are that, although it is necessary to model the formant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 49 publications
3
118
0
3
Order By: Relevance
“…For the present investigation, spectra were extracted at the temporal midpoint in /s/ between these two boundaries. The spectra were then parameterized firstly by converting the frequency axis in Hz to the Bark scale and then by obtaining cepstrally smoothed spectra based on summing the first 10 coefficients after the application of the discrete cosine transformation to these Bark scaled spectra (Watson & Harrington 1999). Finally, a procedure was applied to each such spectrum in turn to obtain the frequency between 2500 Hz and 10000 Hz at which a spectral peak occurred.…”
Section: Methodsmentioning
confidence: 99%
“…For the present investigation, spectra were extracted at the temporal midpoint in /s/ between these two boundaries. The spectra were then parameterized firstly by converting the frequency axis in Hz to the Bark scale and then by obtaining cepstrally smoothed spectra based on summing the first 10 coefficients after the application of the discrete cosine transformation to these Bark scaled spectra (Watson & Harrington 1999). Finally, a procedure was applied to each such spectrum in turn to obtain the frequency between 2500 Hz and 10000 Hz at which a spectral peak occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic variations at the vowel target do exist in naturally produced nominal monophthongs and have been found in selective acoustic studies of American, Canadian, and Australian English vowels ͑e.g., Andruski and Nearey, 1992;Hillenbrand et al, 1995;Watson and Harrington, 1999͒. Yet, there is no acoustic evidence that vowel-inherent spectral change may actually vary systematically across geographic regions of the country and that the use of time-varying features may be a subject to regional variation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that both models performed equally well in differentiating monophthongs when durational data were included, suggesting that the formant on-glide and off-glide are not critical to the distinction of the long/short vowel pairs. An examination of Watson and Harrington's (1999) results shows that excluding duration from the input data greatly reduced the ability of both models to correctly classify /AE+/ and /AE/. For instance, when duration was excluded from the DCT model, the classification scores for /AE+/ dropped from 98.5% to 67.6% correct for females and 98.4% to 77.4% correct for males.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the minimal difference at the steady state of the vowels, it is possible that some spectral differences might persist in terms of the on-glide to and off-glide away from the steady state (Bernard, 1970). Watson and Harrington (1999) used a set of Gaussian classification experiments to establish the degree to which AusE vowels could be separated from each other. They compared a simple "target" model with a "dynamic" model of the vowel formant contour based on discrete cosine transform (DCT) coefficients.…”
Section: Introductionmentioning
confidence: 99%